2020
DOI: 10.1002/open.202000259
|View full text |Cite
|
Sign up to set email alerts
|

In the footsteps of August Michaelis: Syntheses and Thermodynamics of Extremely Low‐Volatile Ionic Liquids

Abstract: A series of nine different known ionic liquids or low melting salts was synthesised and purified. They are composed of the [NTf2]– (bis(trifluoromethane)sulfonimide), [OTf]– (trifluoro‐methane‐sulfonate), or [B(CN)4]– (tetracyanidoborate) anion and [Ph4P]+ (tetraphenylphosphonium), [Ph3BzP]+ (triphenylbenzyl phosphonium), [nBu4P]+ (tetra‐nbutylphosphonium), [nBuPh3P]+ (tri‐phenyl‐nbutylphosphonium), [nBu4N]+ (tetra‐nbutylammonium), or the [PPN]+ (bis(triphenylphosphine)iminium) cation. Precise vapour pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…For the presently investigated ionic liquids, it varies from 136 ± 18 kJ/mol for m-C 6 H 4 (CH 2 ImMe)][NTf 2 ] 2 to 147 ± 12 and 147 ± 13 kJ/mol for [DABCO10][NTf 2 ] and [p-C 6 H 4 (CH 2 ImBu)][NTf 2 ] 2 , respectively, and finally to 180 ± 17 kJ/mol for [C 6 Py][NTf 2 ]. These values are consistent with those previously reported for the other ionic liquids [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For the presently investigated ionic liquids, it varies from 136 ± 18 kJ/mol for m-C 6 H 4 (CH 2 ImMe)][NTf 2 ] 2 to 147 ± 12 and 147 ± 13 kJ/mol for [DABCO10][NTf 2 ] and [p-C 6 H 4 (CH 2 ImBu)][NTf 2 ] 2 , respectively, and finally to 180 ± 17 kJ/mol for [C 6 Py][NTf 2 ]. These values are consistent with those previously reported for the other ionic liquids [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 93%
“…ILs containing the diethyl phosphate [ 25 ], thiocyanate [ 26 ], methanesulfonate [ 27 ], formate and acetate [ 28 ] anions displayed high values of the vapor pressure, while those based on the iodide, bromide or chlorine anions have extremely low values of p v [ 29 , 30 ]. ILs containing the B(CN) 4 anion have p v comparable to that of NTf 2 samples [ 31 ]. Bulow et al reported a comparison of the vapor pressure of ILs containing the same 1-ethyl-3-methyl-imidazolium cation and a series of anions, such as PF 6 , B(CN) 4 , (C 2 H 5 O) 2 PO 2 , NTf 2 , SCN, CF 3 CO 2 , CF 3 SO 3 , BF 4 , C(CN) 3 , (C 2 F 5 ) 3 PF 3 , 4-CH 3 -Ph-SO 3 [ 32 ].…”
Section: Introductionmentioning
confidence: 99%